2022
DOI: 10.1111/jai.14351
|View full text |Cite
|
Sign up to set email alerts
|

Responses by hybrid carp, Barbonymus gonionotus ♀ × Hypsibarbus wetmorei ♂, FED diets containing selected leafmeals

Abstract: In a 56‐day feeding trial, the effects of dietary inclusion of four fibre‐rich‐leaf meal‐based diets (Napier, alfalfa, Gliricidia, or Ipomea) on growth, haemato‐biochemical parameters, and histology of the intestine, liver, and kidney in hybrid lemon fin barb fingerlings were investigated. Each of the leaf meals was included at 10 g 100 g−1 in five dietary treatments. As a control, a diet with no leaf meal was used. Each diet was randomly allocated to three tanks and the hybrid fish were also randomly stocked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Ravardshiri et al (2021) reported a non-significant increase in these parameters for rainbow trout fed cinnamon-supplemented carbohydrate diets. Jimoh et al (2022c) made a similar observation when selected leafmeals were fed to hybrid carp (Barbonymus gonionotus♀× Hypsibarbus wetmorei ♂). In addition to their usual function in blood clotting, platelets are known to have a significant role in innate immunological and inflammatory responses (Holinstat 2017).…”
mentioning
confidence: 56%
“…Ravardshiri et al (2021) reported a non-significant increase in these parameters for rainbow trout fed cinnamon-supplemented carbohydrate diets. Jimoh et al (2022c) made a similar observation when selected leafmeals were fed to hybrid carp (Barbonymus gonionotus♀× Hypsibarbus wetmorei ♂). In addition to their usual function in blood clotting, platelets are known to have a significant role in innate immunological and inflammatory responses (Holinstat 2017).…”
mentioning
confidence: 56%